Climate-induced Displacement and Migration: A Proposed Framework for the G20 for Collaboration1 - Sarkar, Sampurna; Danda, Anamitra Anurag (Journal of Infrastructure Development, 2023)
The impacts of climate change could displace up to 250 million people by 2050, exacerbating poverty and inequality, and derailing the achievement of SDGs by several decades. The impacts of climate change on countries of the Global South are disproportionate. In these countries, large-scale sudden displacement could lead to violations of people's rights. These negative consequences could be avoided through policy interventions aimed at empowering and enhancing human capital. In countries of the Global North, population shrinkage and eventual economic dysfunction are inevitable, but these could be addressed through immigration. Collaboration between countries likely to witness climate change-induced displacement at scale, and those that require immigrants to sustain and grow their populations and economies, could result in positive outcomes for both sets of countries. This Policy Brief makes the above argument through illustrative cases.
Keywords: Climate Change; Climate-Induced Displacement; G20 for Collaboration; Global South; Migration